ANALISIS PERLAKUAN AKUNTANSI PIUTANG DI PT. SUCOFINDO (PERSERO) CABANG JAKARTA - Manuel, Aprilia V.; Manossoh, Hendrik; Affandi, Dhullo (Universitas Sam Ratulangi, 2017)
The company basically runs its business through the sale of goods or services every day that will generate revenue for the company. Receivables are considered very important because it is one component in the balance sheet, so accuracy in processing receivables greatly affect the fairness of its valuation in the financial statements. And the appropriate Financial Accounting Standards are very important in presenting the financial statements because accounting standards provide information to users of financial statements regarding the financial position, results of operations, and other matters relating to the company. The purpose of this study is to analyze the suitability of accounting treatment of PT. SUCOFINDO (Persero) Jakarta branch with the applicable financial accounting standards and formulate accounting standards for receivables that must be used by PT. SUCOFINDO (Persero) Jakarta branch. This research was conducted by qualitative descriptive method. The results of this study show that the accounting treatment of PT. SUCOFINDO (Persero) Jakarta Branch is not in accordance with the applicable financial accounting standards because the presentation of receivables in the financial statements is presented in the net amount, and the recording of receivables written-off is written off into other income accounts. As a suggestion that PT. SUCOFINDO (Persero) represents accounts receivable in the statement of financial position with gross amount followed by estimated uncollectible amounts, and returns the receivables written off to accounts receivable and allowance for doubtful accounts and cash accounts and accounts receivable as deductions on receivables so that the presentation of accounts receivable in accordance with applicable financial accounting standards.Keywords : Accounting treatment of receivables, Statement of Financial Accounting Standards